Suppressors of cytokine signalling (SOCS) are reduced in osteoarthritis - de Andrés, María C. (2011)
OBJECTIVES: Suppressor of cytokine signalling (SOCS) proteins are inhibitors of cytokine signalling that function via the JAK/STAT pathway (Janus kinase/signal transducers and activators of transcription). Eight SOCS proteins, SOCS1–SOCS7 and CIS-1 (cytokine-inducible SH2-domain, with similar structure to the other SOCS proteins) have been identified, of which SOCS1, 2, and 3 and CIS-1 are the best characterised. A characteristic feature of osteoarthritis (OA) is increased production by articular chondrocytes of proinflammatory cytokines, such as interleukin-1 beta (IL-1β) and tumor necrosis factor alpha (TNFα), which may be induced by mechanotransduction and contribute to cartilage destruction. In this study, we have compared the gene expression of SOCS1, 2, 3 and CIS-1 in healthy and OA human chondrocytes, and also analyzed the effects of IL-1β and TNFα on the levels of mRNA encoding these SOCS family members. In addition, SOCS2 protein production was assessed and the CpG methylation status of the SOCS2 promoter was analyzed to determine the role of epigenetics in its regulation. METHODS: Femoral heads were obtained after joint replacement surgery for late stage OA and hemiarthroplasty following a fracture of the neck of femur (#NOF). Chondrocytes from the superficial layer of OA cartilage and the deep zone of #NOF cartilage were isolated by sequential treatment with trypsin, hyaluronidase and collagenase B. Total DNA and RNA were extracted from the same chondrocytes, and the levels of SOCS1, 2, 3 and CIS-1 mRNA were determined by qRT-PCR. The percentage of methylation in the CpG sites of the SOCS2 proximal promoter was quantified by pyrosequencing. Alternatively, healthy chondrocytes were isolated from #NOF cartilage and cultured with and without a mixture of IL-1β and oncostatin M (OSM, both 2.5 ng/ml) or TNFα (10 ng/ml). The short-term cultures with single cytokine treatment were harvested 24 and 72 h after treatment, and the long-term cultures were maintained for 4–5 weeks until confluent with periodical cytokine stimulation. Total RNA was extracted and mRNA levels were determined by qRT-PCR. RESULTS: The SOCS2 and CIS-1 mRNA levels were reduced by approximately 10-fold in OA samples compared to control samples, while SOCS1 and SOCS3 showed similar expression patterns in OA and control chondrocytes. The SOCS2 and CIS-1 mRNA levels declined by 6-fold and 3-fold with long-term treatment with IL-1β and OSM in combination and TNFα, respectively. There was no significant difference in the CpG methylation status of the SOCS2 promoter between healthy and OA chondrocytes. Similarly, cytokine stimulation did not change the CpG methylation status of the SOCS2 promoter. CONCLUSIONS: This study demonstrates the reduced expression of SOCS2 and CIS-1 in OA, while SOCS1 and SOCS3 were unaffected. The observation that long-term treatment with inflammatory cytokines attenuated the expression of SOCS2 and CIS-1 suggests a potential positive feedback mechanism, and a role of SOCS in the pathology of OA.